Kiindulópontok és kontextusok Fazekas Mihály életművének újraértelmezéséhez - Debreczeni, Attila (Studia Litteraria, 2020)
The first part of the study gives a summary of the textological approach to the oeuvre of Mihály Fazekas, detailed elsewhere. Kis is followed by the highlighting of four contexts grouped around the concepts of Poetry, Morals, Sciences and Interpretation of self, all of which focus on a text source or group of text sources. The connection between the chapters is built retroactively, later chapters and the points discussed therein refer back to relevant concepts in previous ones. After the description of the possible contexts, the last chapter discusses the different aspects for the evaluation of the whole oeuvre, and gives a number of hypotheses, hoping to inspire further research.